Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-03-09T14:52:27+01:00
A. 2 (x-3) (2x-1)
=2(2x²-x-6x+3)
=4x²-14x+6

B. (2x-5) ²
=4x²-20x+25

C. (8x-1) (3x-2)
=24x²-16x-3x+2
=24x²-19x+2

D. (4x+1) (2x-1) (3x+2)

=(8x²+2x-4x-1)(3x+2)
=(8x²-2x-1)(3x+2)
=24x³-6x²-3x+16x²-4x+2
=24x³+10x²-7x+2
2014-03-09T14:55:21+01:00
A) 2(x-3)(2x-1) = 2(2x²-x-6x+3) = 4x²-2x-12x+6 = 4x²-14x+6
B) (2x-5) = 2x-5
C) (8x-1)(3x-2) = 24x²-16x-3x+2 = 24x²-19x+2
D) (4x+1)(2x-1)(3x+2) = (4x-1)(6x²+4x-3x-2) = 24x^3 + 16x² - 12x² - 8x - 6x² - 4x + 3x + 2 = 24x^3 - 2x² - 9x + 2

Vérifie si je n'ai pas fais d'erreurs stp !